Israel : Staff Report for the 2003 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This 2003 Article IV Consultation highlights that Israel's economy has entered a modest recovery path, after almost three years of recession. Led by external demand, real GDP is estimated to have grown 1.3 percent in 2003, despite anemic investment. Furthermore, high frequency indicators suggest that output is recovering, private consumption is growing, and tourism is rebounding. The external current account deficit continues to fall and is now close to balance. The sizable capital outflow of the last quarter of 2002 and the first quarter of 2003 has been reversed, and foreign direct investment has rebounded.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet